2021
DOI: 10.1186/s43045-021-00086-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obsessive-compulsive disorder (OCD) among Iraqi undergraduate medical students in time of COVID-19 pandemic

Abstract: Background Obsessive-compulsive disorder (OCD) is a common mental disorder affecting millions of people. Its onset and peak are during late teens making university students a priority target. Medical student perhaps is at greater risk for developing OCD while corona COVID-19 is expected to more exaggerate symptoms mainly with extra hygiene and cleanliness practices. The aim of the study was to estimate the prevalence of OCD symptoms among Iraqi medical students, and to assess the associated psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 26 publications
3
58
2
2
Order By: Relevance
“…A similar prevalence of OCD symptoms was reported in earlier studies conducted during the pandemic among the general population in Saudi Arabia with 62.4% and in Canada with 60.3% for obsessions, and 53.8% for compulsions, and a prevalence of 43% among medical students in Iraq. 9,15,16 Also, moderate/high perceived stress was reported in 84.9% of the Canadian general population and 85.2% of students in virtual classrooms in Saudi Arabia during the pandemic. 5,9 It is possible that we might also observe an increase in the number of OCD patients in the upcoming period.…”
Section: Only During Covid-19 Pandemic N (%)mentioning
confidence: 99%
See 3 more Smart Citations
“…A similar prevalence of OCD symptoms was reported in earlier studies conducted during the pandemic among the general population in Saudi Arabia with 62.4% and in Canada with 60.3% for obsessions, and 53.8% for compulsions, and a prevalence of 43% among medical students in Iraq. 9,15,16 Also, moderate/high perceived stress was reported in 84.9% of the Canadian general population and 85.2% of students in virtual classrooms in Saudi Arabia during the pandemic. 5,9 It is possible that we might also observe an increase in the number of OCD patients in the upcoming period.…”
Section: Only During Covid-19 Pandemic N (%)mentioning
confidence: 99%
“…The psychological symptoms associated with OCD that were reported in previous studies include stress, anxiety, depression, and sleep disorders. 9,15,20 And OCD was generally linked to stressful life events. 21,22 In this study, we also found that new-onset dirt, germs, and virus obsessions were significantly higher among the 40-49 year-old age group (63%), employed (60.3%), housewives (59.6%), students (58.2%), quarantine discipliners (62.6%), and those who spent 20 or more days in quarantine (58.7%, 58.6% and 56%).…”
Section: Only During Covid-19 Pandemic N (%)mentioning
confidence: 99%
See 2 more Smart Citations
“…As undergraduate medical students are closely associated with health care workers, they are susceptible to experience similar psychological and emotional distress. Also, their dense curriculum, limited leisure time, the stressful nature of medical schools, and as the medical students are asked to be more precise, perfect, and obsessive a little bit more, they are at high risk for developing OCD (43)(44)(45).…”
Section: Introductionmentioning
confidence: 99%